ACU193: An Immunotherapeutic Poised to Test the Amyloid β Oligomer Hypothesis of Alzheimer’s Disease - Krafft, Grant A.; Jerecic, Jasna; Siemers, Eric; Cline, Erika N. (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is an age-related neurodegenerative disease that affects 50M people worldwide, with 10M new cases occurring each year. The emotional and economic impacts of AD on patients and families are devastating. Approved treatments confer modest improvement in symptoms, and recently one treatment obtained accelerated approval from the US Food and Drug Administration (FDA) and may have modest disease modifying benefit. Research over the past three decades has established a clear causal linkage between AD and elevated brain levels of amyloid β (Aβ) peptide, and substantial evidence now implicates soluble, non-fibrillar amyloid β oligomers (AβOs) as the molecular assemblies directly responsible for AD-associated memory and cognitive failure and accompanying progressive neurodegeneration. The widely recognized linkage of elevated Aβ and AD spawned a comprehensive 20-year therapeutic campaign that focused primarily on two strategies – inhibition of the secretase enzymes responsible for Aβ production and clearance of Aβ peptide or amyloid plaques with Aβ-directed immunotherapeutics. Unfortunately, all clinical trials of secretase inhibitors were unsuccessful. Of the completed phase 3 immunotherapy programs, bapineuzumab (targeting amyloid plaque) and solanezumab (targeting Aβ monomers) were negative, and the crenezumab program (targeting Aβ monomers and to a small extent oligomers) was stopped for futility. Aducanumab (targeting amyloid plaques), which recently received FDA accelerated approval, had one positive and one negative Phase 3 trial. More than 25 negative randomized clinical trials (RCTs) have evaluated Aβ-targeting therapeutics, yet none has directly evaluated whether selective blockage of disease-relevant AβOs can stop or reverse AD-associated cognitive decline. Here, we briefly summarize studies that establish the AD therapeutic rationale to target AβOs selectively, and we describe ACU193, the first AβO-selective immunotherapeutic to enter human clinical trials and the first positioned to test the AβO hypothesis of Alzheimer’s disease.